(untitled) (Research, Society and Development, 2022)
This article aims to evaluate the foundation behavior of a wind turbine located in northeastern Brazil. The original design of the foundation of the tower did not consider the raft-soil contact in the performance of the system. In this way, the present work proposes to consider the raft-soil contact, that is, to assume that the foundation is a piled raft and to evaluate the impact of this premise on the foundation’s performance. The analyzes were carried out in two finite element software: ABAQUS and Plaxis 3D Foundation, adopting different modeling criteria for the software. The geotechnical characterization of the site was carried out through SPT soundings and back-calculations of a load test. The results obtained through ABAQUS and Plaxis 3D were in agreement, despite the particularities of modeling adopted in each software. The results showed that the raft supported more than 60% of the vertical load applied on the foundation, attesting to its importance in this case. The foundation met the stiffness and safety criteria with a certain clearance, which indicates the possibility of optimizing the system, with a reduction in the number of piles, for example.